Refined Finite Element Analysis of Crack Causes in SRC Arch Rib Bridges considering Multiple Factors. (15th November 2018) - Yu, Mengsheng; Deng, Nianchun; Chen, Qifeng; Hao, Tianzhi
Abstract : The SRC (steel-frame reinforced concrete) arch bridge is an important part of the development of arch bridges. Scholars worldwide have studied it from various aspects because of its stronger stiffness and stability than other types of bridges especially when crossing the canyon. The steel frame is a stress bracket during construction. Concrete becomes the main axial-pressure bearing structure when it fills the inner pipe and the encased frame. This article mainly focuses on the crack problems of SRC arch bridging during the postconstruction operation, local model of the midspan arch rib, and the equivalent relationship between the coefficient of expansion and the temperature of concrete. This study uses a cooling method to simulate the shrinkage process with detailed analysis of three properties including concrete shrinkage, temperature gradients, and concentrated hanger rod force. It is concluded that the SRC arch bridge will have large tensile stress on both inner and outer surfaces of slab and web when the temperature changes, and it is the main cause of cracks. The results agree well with measured data. At last, we come up with some reference suggestions in the design and construction of similar bridges in the future.